'Once, there was a life, a life that someone could not enjoy': Learning and development in an action research project. (2nd January 2019) - Csillag, Sara
ABSTRACT: Action research is participative research, involving all stakeholders in the research process on a voluntary basis. Its main objective is to create practical knowledge, which supports stakeholders in everyday professional processes. The creation and utilization of this kind of knowledge, the facilitation of individual and group level action learning contributes to the achievement of social and community objectives as well. In our present account we aim to give a brief insight into the process and results of a one-and-a-half-year long project conducted at several levels and locations – a development project designed to enhance the quality of life for people with autism. Connected to the process and results of the research project we would like to discuss some interesting features of the action learning the participants experienced in the process.